THE ELEMENTARY STUDENTS’ CONCEPT OF ISLAMIC EDUCATION: THE IMPACT OF THE FULL DAY SCHOOL - Rahamma, Tawany; Elihami, Elihami; Dangnga, Muhammad Siri; Ali, Sitti Nurhayati (Al-Mirah: Jurnal Pendidikan Islam, 2019)
The purpose of this study is to teach and learning in the Elementary School as a Elementary School involved in education and teaching is to use full day school system to provide feedback to students through Islamic Education. The qualitative-based research methodology is characteristic evaluation involving non-participant observation, interview, and documentation. This study aims to find out how the implementation of full day school affects the level of involvement of student participation. The survey items selected for this study are authorized and the field research of activity. In the aspect of student involvement, it is generally reported to have a positive attitude involved in education and teaching is to use full day school system. Participating in full day school using the full day school is a strong positive experience for students from the Elementary School. The student’s vision of the benefits of full day school learning through Islamic education was very good. The students as prospective teachers in the sample as a whole tend to assess program of the government the use of student response systems in improving learning